Fieldwork, Herbarium Revisions, and DNA Barcodes: Basic Ingredients to Shed Light on the Dark Realms of Plant Biodiversity, an Example with Two Enigmatic Andean Carex (Cyperaceae) Species - Morales-Alonso, Ana (2024)
Two recent fieldwork expeditions to Peru and Ecuador resulted in the finding of two Carex species (C. hypsipedos and C. sanctae-marthae) previously known from a single collection each, and of uncertain morphological and systematic affinities. We performed phylogenetic analyses using barcode molecular markers and a detailed morphological comparison among the new specimens and the original collections. A BLAST search was used to obtain the preliminary infrageneric affinities of problematic samples. Phylogenetic results confirmed the adscription of these species to two sectional Carex groups: Carex sect. Racemosae (subg. Carex) for C. hypsipedos and Carex sect. Junciformes (subg. Psyllophorae) for C. sanctae-marthae. Morphological revision revealed unique traits in C. hypsipedos, especially geocarpy, here strikingly reported for the first time for the genus Carex. On the other hand, the careful comparison of the new materials of C. sanctae-marthae revealed unequivocal affinities with the type, confirming its identity as this species. Our work illustrated that for the understanding of poorly known groups, such as these two Neotropical Carex, integrative approaches combining basic biosystematics tools are still very necessary: field and herbaria surveys and DNA barcode.